Job insecurity dan konsekuensinya pada kecemasan karyawan di saat pandemi COVID-19: peran God locus of control - Achmadi Achmadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
The purpose of this study was to examine the relationship between job insecurity and employee anxiety while at the same time identifying coping strategies that could withstand the adverse effects of job insecurity by placing a God locus of control (GLC). A total of 132 employees from several companies were involved in this study. This study shows that Job insecurity positively affects employee anxiety levels. God's locus of control negatively affects anxiety and acts as a boundary condition to reduce the effect of job insecurity on employee anxiety. The analysis results provide knowledge relevant to the scientific literature related to the study of job insecurity and practical implications for reducing the effect of this phenomenon on employee anxiety levels amid the COVID-19 pandemic.